Respuesta :
[tex]\dfrac{18r^4s^5t^6}{-3r^2st^3}=\dfrac{18}{-3}r^{4-2}s^{5-1}t^{6-3}=-6r^2s^4t^3[/tex]
or (C)
or (C)
Answer:
Option (C) is correct.
Thus, the result of [tex]\frac{18r^4s^5t^6}{-3r^2st^3}=-6r^2s^4t^3[/tex]
Step-by-step explanation:
Given: expression [tex]\frac{18r^4s^5t^6}{-3r^2st^3}[/tex]
We have to find the value of given expression and choose a correct option from the given options.
Consider the given expression [tex]\frac{18r^4s^5t^6}{-3r^2st^3}[/tex]
Apply fraction rule,[tex]\frac{a}{-b}=-\frac{a}{b}[/tex]
We have,
[tex]=-\frac{18r^4s^5t^6}{3r^2st^3}[/tex]
Divide 18 by 3 , we get 6,
[tex]=\frac{6r^4s^5t^6}{r^2st^3}[/tex]
Apply exponent rule [tex]\frac{x^a}{x^b}\:=\:x^{a-b}[/tex]
[tex]\frac{r^4}{r^2}=r^{4-2}=r^2\\\\ \frac{t^6}{t^3}=t^{6-3}=t^3\\\\ \frac{s^5}{s}=s^{5-1}=s^4[/tex]
we get,
[tex]=-6r^2s^4t^3[/tex]
Thus, the result of [tex]\frac{18r^4s^5t^6}{-3r^2st^3}=-6r^2s^4t^3[/tex]
Option (C) is correct.